Pengaruh pemakaian bahan restorasi mahkota terhadap kesehatan jaringanperiodontal Effect of using crown restoration material to the health of periodontal tissue - Edy Machmud; Herawati Herawati (DiscoverSys Inc., 2012)
Using crown as restoration to replace missing natural teeth is currently very popular. Successful restoration is therestoration that can last in a long time in the oral cavity. But sometimes there is a result of the use of restorativematerials that can’t be accepted by the body tissues. Therefore this study with a quasi experimental longitudinal designwith samples of 100 people user crown (porcelain, acrylic and metal crown). Prior using denture, the patient is given adental health education (DHE) and tartar cleaning and maintenance agreement. CPITN examination for signs ofinflammation (gingival discoloration, gingival bleeding, calculus and pocket depth) before and after the use of crown3, 6 and 12 months. Data were collected and analyzed by independent t-test. The results showed that there weresignificant differences in the results at month 3 to month 6, and month 6 to month 12 in acrylic and metal restoration(P <0.05). While the porcelain restoration is no significant difference in outcome between treatments at months 3, 6and 12 (P> 0.05). It was concluded that the porcelain restoration is a material that can be accepted by the body because it does not cause gingival inflammation.